Photoactivatable aggregation-induced emission probes for lipid droplets-specific live cell imaging. Issue 3 (6th January 2017) - Gao, Meng; Su, Huifang; Lin, Yuhan; Ling, Xia; Li, Shiwu; Qin, Anjun; Tang, Ben Zhong
Abstract : Photoactivatable probes for lipid droplets (LDs)-specific live-cell imaging are powerful tools for investigating their biological functions through precise spatial and temporal control. Abstract : Photoactivatable probes for lipid droplets (LDs)-specific live-cell imaging are powerful tools for investigating their biological functions through precise spatial and temporal control. Ideal photoactivatable probes for LDs imaging require high concentration accumulation of fluorophores in LDs, simple synthetic procedures, and excellent photoactivation efficiency. However, it is difficult to overcome these challenges by conventional fluorophores due to aggregation-caused quenching (ACQ). In this study, a new class of photoactivatable and LDs-specific fluorescent probes was developed based on dihydro-2-azafluorenones, which can easily undergo photooxidative dehydrogenation reaction to afford 2-azafluorenones with aggregation-induced emission (AIE) properties. Dihydro-2-azafluorenones as photoactivatable and LDs-specific probes display significant advantages of excellent photoactivation efficiency and lack of self-quenching in the aggregated state, and are expected to have broad applications in study of biological functions of LDs' through light-controlled spatiotemporal imaging.